Hardware Technologies for High-Performance Data-Intensive Computing. - Gokhale, Maya; Cohen, Jonathan; Yoo, Andy; Miller, W. Marcus; Jacob, Arpith; Ulmer, Craig; Pearce, Roger (Computer (00189162), 2008)
The article offers an investigation into hardware platforms suitable for data-intensive systems. It evaluates the benefits of two coprocessor architectures: graphics processors and reconfigurable hardware. It describes the Large Synoptic Survey Telescope (LSST) and the image-processing benchmark, the Lanczos resampling filter. To assess the potential for accelerating LSST image-processing tasks, the authors' used the Lanczos filter. A key step in processing large document streams is language classification.